Radio and Women's Empowerment in Francophone West Africa - Heywood, Emma (Palgrave Studies in Communication for Social Change,, 2024)
This open access book breaks new ground by examining the significant role played by radio in empowering women in three Francophone West African countries: Mali, Niger and Burkina Faso. It examines the representation and perception of key themes broadcast by radio and associated with women's empowerment in the three countries. Each chapter contextualises a specific topic in the country and then explores discrete aspects of radio's provision. The topics covered in the chapters are women's political engagement; women and finances; women and life within marriage; inheritance; women's involvement in radio structures; and radio, internally displaced women, and trauma. Given the social, economic and political vulnerability and deteriorating security situation of the three countries, this book provides a timely and meaningful contribution to acknowledging and understanding the vital role of radio in women's empowerment. Emma Heywood is a Senior Lecturer in Journalism, Radio and Communication at the University of Sheffield. Her research focuses on the role and impact of radio in conflict-affected areas, particularly regarding perceptions and representations of women's rights and empowerment in Mali, Niger, Burkina Faso.